(In)segurança hídrica e o desafio de viver e produzir no PDS Sepé Tiaraju, SP - Lucati, Leticia Bolonha (2021)
The water management in the settlements of the brazilian Agrarian Reform is a topic of great relevance and always current, due to its complexity and developments. Amidst the current environmental crisis, therefore, debates about the importance and process of water scarcity are even more present. Recognizing the importance of water for domestic and productive uses, this work sought to describe the characteristics related to water supply and management in the SDP Sepé Tiaraju, by the own settlers, through their speeches. The study area is located on the recharge area of the Guarani aquifer, in the cities of Serra Azul and Serrana. The settlement is an example of agroecological production amid the highest concentration of sugarcane in Brazil. Questions about the sources of supply, distribution and uses of water in everyday life were adressed. To understand the experiences of farmers related about the water, qualitative and quantitative approaches were chosen, through the application of questionnaires and semi-structured interviews with 10 farmers from all nucleus of the settlement. Data analysis was performed based on the interdisciplinarity that the central theme requires. The results indicate that problems related to water supply and its multiple uses have existed for years on SDP, pointing to a situation of human and productive vulnerability over all the life cycles of the settlement, which goes against the construction of the guiding principles of the SDP modality: the construction of a rural settlement model, in which Agroecology is the center of the technological matrix. It is considered urgent the strengthening of public policies aimed at water supply for family farming, as well as basic sanitation in general.